Law Number 35 of 2014, Article 54, Concerning Child Protection at Kartika 1-2 Medan High School - Siregar, Dahris; Al Habsyi , Bobby; Sitepu, Karolina; Darma, Mospa (Innovative: Journal Of Social Science Research, 2024)
Many educational institutions experience psychological, physical, and even sexual violence. Every unit of education must be protected and prevented. This study aims to investigate whether the Kartika I-2 education unit of Medan High School is subject applied to the implementation of Law Number 35 of 2014's Article 54 regarding child protection. As per Article 54, children and students are entitled to legal protection against various forms of violence perpetrated by teachers, education staff and fellow students in the school environment. The researcher used an empirical juridical approach in this study to explain how Child Protection Law Number 35 of 2014, Article 54 as a student is applied in Kartika I-2 High School Medan., both in terms of prevention and prevention efforts in providing protection, and everything that hinders the implementation of Child Protection Law Number 35 of 2014, Article 54, both from internal and external sources, also explained how Kartika I-2 Medan High School handled challenges. Researchers obtain data from primary and secondary data. This study used descriptive analysis and qualitative data analysis. Kartika I-2 Medan High School makes pre-emptive efforts by making decisions and forming a team for prevention and handling of violence in education units (TPPK), prevention efforts through the implementation of school programs that prioritize supervision and prevention. Internal factors, such as individual factors of students, parents/guardians, and educators, as well as external factors, such as differences in rules of conduct with other schools, are obstacles faced by Kartika I-2 Medan High School, there are new regulations, living quarters and social environments, technological advances and new cultures. Kartika I-2 Medan High School uses an existing program to address this problem.